2008
DOI: 10.1159/000178756
|View full text |Cite
|
Sign up to set email alerts
|

Serum Amyloid P Component as a Biomarker in Mild Cognitive Impairment and Alzheimer’s Disease

Abstract: Background: Serum amyloid P component (SAP), present in amyloid-β (Aβ) plaques in Alzheimer’s disease (AD), may protect Aβ deposits against proteolysis, thereby promoting plaque formation. The aim was to investigate if SAP levels in cerebrospinal fluid (CSF) and serum can be used to discriminate controls, AD and mild cognitive impairment (MCI) patients, and to identify incipient AD among MCI patients. Methods: SAP levels in CSF and serum were determined in 30 controls, 67 MCI and 144 AD patients. At follow-up,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 58 publications
2
16
1
Order By: Relevance
“…SAP does not readily cross the blood brain barrier; however, neurons in the brain can produce SAP, and this production is upregulated in AD brains [8] although there is no difference in the cerebrospinal fluid (CSF) levels of SAP between AD patients and age-matched normal controls [911]. Among AD patients, one study using 70 patients found that higher CSF levels of SAP tended to correlate with less dementia (9), while a smaller study using 20 patients did not observe any trend (10).…”
Section: Introductionmentioning
confidence: 99%
“…SAP does not readily cross the blood brain barrier; however, neurons in the brain can produce SAP, and this production is upregulated in AD brains [8] although there is no difference in the cerebrospinal fluid (CSF) levels of SAP between AD patients and age-matched normal controls [911]. Among AD patients, one study using 70 patients found that higher CSF levels of SAP tended to correlate with less dementia (9), while a smaller study using 20 patients did not observe any trend (10).…”
Section: Introductionmentioning
confidence: 99%
“…This effl ux mechanism can explain the very low CSF index values for SAP observed by Mulder et al [37]. However, the reduction of CSF SAP levels found in demented AD brains may also suggest that SAP located in brain interstitial fl uid is quickly deposited to amyloid plaques [34,36,37].…”
Section: Discussionmentioning
confidence: 99%
“…However, no signifi cant increase in SAP production could be detected in postmortem samples from hippocampus and frontal cortex of nondemented subjects with AD neuropathology [32]. Available data about SAP levels in cerebrospinal fl uid (CSF) of AD patients are controversial: a study showed elevated SAP concentration [33], whereas the others [34][35][36][37] did not detect signifi cant differences between AD and age-matched control patients. However, CSF SAP level correlated with cognitive function measured by Mini-Mental State Examination [34], and a low value was associated with two-fold increased risk of progression to AD in case of mild cognitive impairment patients [36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the major acute-phase protein SAP (Serum amyloid P component) has lower levels in MCI patients who progressed to AD than in those who did not progress to AD [164], suggesting that low SAP levels are linked to an increased risk of progression to AD.…”
Section: Inflammatory Cytokinesmentioning
confidence: 99%